Cor triatriatum dextrum – An Unusual Variant of Triatrial Heart - Topuzović, N.; Karner, I.; Rusić, A.; Krstonošić, B.; Jurić, M.; Giesler, O.; Kristek, B.; Mrdjenović, S. (Nuklearmedizin - NuclearMedicine, 1996)
The present report describes a rare case of triatrial heart, cor triatriatum dextrum in a 31-year-old woman in whom the anomaly was incidentally detected by radionuclide angiocardiography. Subsequent assessment with two-dimensional echocardiography and right heart catheterization confirmed the presence of a membrane subdividing the right atrium into two distinct chambers. To the best of our knowledge, this is the only case in which this cardiac anomaly was demonstrated by radionuclide technique.Der vorliegende Bericht behandelt einen seltenen Fall von Cor triatriatum dextrum bei einer 31jährigen Frau, bei der diese Anomalie mit Hilfe der radionukliden Angiokardiographie entdeckt wurde. Mit Hilfe der zweidimensionalen Echokardiographie und der Katheteruntersuchung des rechten Herzens wurde das Bestehen einer Membrane, die das rechte Atrium in zwei getrennte Kammern teilt, bestätigt. Soviel wir wissen, ist das der einzige Fall, bei dem diese Herzanomalie mit Hilfe der radionukliden Technik nachgewiesen werden konnte.
Keywords: Radionuclide angiocardiography; cor triatriatum dextrum